Answer:
b < -1
Step-by-step explanation:
Step 1: Write inequality
-3(6b - 1) > 18 - 3b
Step 2: Solve for <em>b</em>
<u>Distribute -3:</u> -18b + 3 > 18 - 3b
<u>Add 18b to both sides:</u> 3 > 18 + 15b
<u>Subtract 18 on both sides:</u> -15 > 15b
<u>Divide both sides by 15:</u> -1 > b
<u>Rewrite:</u> b < -1
Answer:
I mean how can I answer this???????????????????????
Answer:
1st, 2nd and 6th options
Step-by-step explanation:
Given
- x +
= 6x ( multiply through by 6 to clear the fractions )
4 - 6x + 1 = 36x ← option 1 will have the same solution set
----------------------------------------------------------------------
Adding the 2 fractions on the left side gives
+
- x = 6x , that is
- x = 6x ← option 2 will have the same solution set
------------------------------------------------------------------------
From
4 - 6x + 1 = 36x ( add 6x to both sides )
5 = 42x ← option 6 will have the same solution set
Answer:
Step-by-step explanation:
let the first angle be 5x
second be 4x
and third be 1x
as we know that by adding all the sides of triangle we get 180°
therefore ,
5x+4x+1x=180°
10x=180°
hence ,
x=18°
first angle - 18*5 = 90°
second angle - 18*4=72°
third angle - 18°
HOPE THIS HELPS YOU !!!